PRINCIPLES OF PUBLIC FUNDS EXPENDITURES UNDER MARTIAL LAW IN UKRAINE - Dmytryk, Olga; Tokarieva, Katerina (Socio-economic relations in the digital society, 2023)
This publication examines the essence and peculiarities of implementing the principles of public fund expenditures under martial law in Ukraine. The authors set the following tasks: to identify a set of principles of public fund expenditures under martial law, to reveal the content of such principles, and to formulate proposals for improving the current budget legislation. To solve the tasks set, the following methods were used in conjunction with each other: induction and deduction, system analysis and synthesis, and comparison. The author emphasizes that the introduction of martial law implies a certain transformation of all spheres of public life compared to their normal functioning and legal regulation, and the establishment of a different from the general (i.e., special) legal regime in various areas of state-building, and in particular, it requires the State to revise the paradigm of expenditures from public funds, and in particular, from the State and local budgets. The author emphasizes that despite the year and a half that has passed since the full-scale invasion; the issues of revising approaches to public expenditures and creating systematic and high-quality regulation of public expenditures in Ukraine remain relevant. The author reveals the content of the principles of the budget system of Ukraine, which are enshrined in national legislation, taking into account the requirements of the legal regime of martial law.